A study of older adults: Observation of ranges of life satisfaction and functioning - Good GA; LaGrow S; Alpass F (New Zealand Psychological Society, 2011)
Levels of daily functioning and life satisfaction in older people are investigated in this study. Surveys and interviews included 425 people aged 65+ and comparisons were made between three age groups (ages 65-74, 75-84, 85 +) on levels of activity, independence and social support; satisfaction with levels of independence, activity and social support and overall life satisfaction, Results indicated that those aged 85+ had significantly lower levels of activity and independence than those in the two younger age groups. Differences were found in 8 of 12 domains of independence and in outdoor work and mobility activities. The oldest age group was also found to be significantly less satisfied with their levels of independence and activity than were the younger age groups. No significant differences were found between the groups in overall life satisfaction. Levels of activity and independence, satisfaction with social support and satisfaction with independence were found to make unique contributions to t to the prediction of variance in overall life satisfaction. Findings are important in understanding what to expect of ourselves and others as we age, which daily activities are likely to be most difficult for older people and what factors are predictors of overall life satisfaction.
Keywords: 1701 Psychology; 1702 Cognitive Sciences